In vivo CT imaging tracking of stem cells labeled with Au nanoparticles. Issue 3 (13th July 2021) - Huang, Jie; Bao, Hongying; Li, Xiaodi; Zhang, Zhijun
Abstract: Stem cell–based therapy offers great promise for a wide range of diseases and injuries that cannot be effectively treated by existing medicine and therapies. However, the translation of stem cell therapy to the clinic is still hampered by the lack of profound understanding about the survival, differentiation, migration, homing, and fate of the transplanted stem cells during the therapy. To address these issues, computed tomography (CT) based on nanomaterials, in particular gold nanoparticles (AuNPs), has been developed for enhanced and long‐term imaging tracking of transplanted stem cells. In this Mini‐Review, we summarize the recent progress in AuNP‐based CT imaging tracking of stem cells, with focuses on new strategies to improve cellular uptake of AuNPs for better CT imaging contrast, and on multimodal imaging tracking of stem cells in vivo . Finally, we discuss the existing challenges and possible future developments of the AuNP‐based CT imaging tracking of stem cells for regenerative medicine and other biomedical applications. Abstract : AuNP‐based CT imaging provides a noninvasive, sensitive, and real‐time cell imaging and tracking strategy for in vitro and in vivo monitoring and in‐depth understanding of the delivery, migration, regenerative ability, and final fate of the transplanted stem cells in stem cell therapy. The work of Jie Huang et al. have systematically summarized the recent advances in AuNP‐based CT imaging tracking of stem cells for various biomedical applications.